Efficiency and Safety of the Selective Relaxant Binding Agent Adamgammadex Sodium for Reversing Rocuronium-Induced Deep Neuromuscular Block: A Single-Center, Open-Label, Dose-Finding, and Phase IIa Study - Zhao, Yanhua; Chen, Sifan; Huai, Xiaorong; Yu, Zhangjie; Qi, Youmiao; Qing, Jie; Yu, Weifeng; Su, Diansan (Frontiers in Medicine, 2021)
Background: Rapid reversal of neuromuscular block after surgery and anesthesia is often necessary. Here, we reported the primary efficacy and safety data from a phase IIa study on adamgammadex sodium, a newly developed modified γ-cyclodextrin derivative. Methods: This was a phase IIa, single-center, randomized, open-label, and dose-finding study that enrolled 35 patients under general anesthesia who received the neuromuscular blocking agent rocuronium for induction and maintenance of neuromuscular blockade. The subjects were randomized to one of the five adamgammadex dose groups (2, 4, 6, 8, and 10 mg kg−1) and to the 4 mg kg−1 sugammadex group. Pharmacological efficacy was the recovery time from the start of adamgammadex or sugammadex administration to train-of-four (TOF) ratio ≥0.9, 0.8, and 0.7 among the different dose groups. Adverse events were recorded throughout the study. Results: The efficacy in reversing deep neuromuscular block was the same between 4 mg kg−1 sugammadex and adamgammadex. However, in the lowest dose groups of 2 and 4 mg kg−1 adamgammadex, adequate reversal could not be achieved in all subjects. The recovery time of TOF ratio to 0.9, 0.8, and 0.7 was shorter in the adamgammadex 10 mg kg−1 group than in the sugammadex 4 mg kg−1 group. The average values of the TOF ratio after 3 min of administration of adamgammadex 8 and 10 mg kg−1 and sugammadex 4 mg kg−1 were >90%. There were no serious adverse events after the use of adamgammadex, and no subjects had to be withdrawn from the trial. Conclusions: Adamgammadex enabled quick, predictable, and tolerable reversion of rocuronium-induced deep neuromuscular block in a dose-dependent manner. Adamgammadex doses of 6–10 mg kg−1 might be the recommended dose range for further exploration of efficacy. Clinical Trial Registration: This study was registered at chictr.org.cn, identifier: ChiCTR2000038391.